The Effect of Citrit Acid-Glucose NADES Ratio on Young Avicennia marina Leaf Extract - Mirza Gulam Ahmad; Hartati Kartikaningsih; Heder Djamaludin; Ravika Indah Kharisma; Gevbry Ranti Ramadhani Simamora; Desy Arisandi; Jeny Ernawati Tambunan; Fahri Sinulingga; Kristina Marsela; Gilang Rusrita Aida (Journal of Fish Health, 2026)
Mangrove ecosystems are widely acknowledged as valuable natural sources of bioactive compounds with potential applications in functional food and pharmaceutical industries. Avicennia marina leaves, in particular, contain diverse secondary metabolites; however, the efficiency of their extraction is strongly influenced by solvent type and polarity. This study aimed to evaluate the effect of different ratios of citric acid–glucose-based natural deep eutectic solvent (NADES) on extraction yield, pH, and phytochemical profile of young A. marina leaf extracts. A Completely Randomized Design (CRD) was applied, consisting of four treatments of citric acid:glucose ratios (1:1, 1:2, 1:3, and 1:4) with four replications. Extraction was performed at 50°C for 60 minutes using a material-to-solvent ratio of 1:20 (w/v). The findings indicated that increasing the proportion of citric acid in the NADES formulation significantly enhanced extraction yield, with the highest yield (20.40%) obtained at the 4:1 ratio. The extract pH ranged from 1.79 to 1.88 and decreased as the citric acid proportion increased. Phytochemical screening confirmed the presence of flavonoids, tannins, and alkaloids, while saponins, steroids, and terpenoids were not detected. Overall, these results demonstrate that citric acid–glucose-based NADES serve as an effective green solvent system for extracting polar bioactive compounds from young A. marina leaves.